2001
DOI: 10.1890/0012-9658(2001)082[3083:frwpiv]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Functional Responses With Predator Interference: Viable Alternatives to the Holling Type Ii Model

Abstract: A predator's per capita feeding rate on prey, or its functional response, provides a foundation for predator-prey theory. Since 1959, Holling's prey-dependent Type II functional response, a model that is a function of prey abundance only, has served as the basis for a large literature on predator-prey theory. We present statistical evidence from 19 predator-prey systems that three predator-dependent functional responses (Beddington-DeAngelis, Crowley-Martin, and Hassell-Varley), i.e., models that are functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
223
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 573 publications
(232 citation statements)
references
References 59 publications
7
223
0
2
Order By: Relevance
“…This result is consistent with the recent suggestion that along the continuum from ratio to prey dependence, intermediate interference will be the most commonly observed level [14-16]. Our study builds on previous reviews in more than doubling the number of unbiased estimates of m analyzed [6,13]. In addition, our study helps to resolve the long-standing debate over whether prey or ratio dependence is the better simplification.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is consistent with the recent suggestion that along the continuum from ratio to prey dependence, intermediate interference will be the most commonly observed level [14-16]. Our study builds on previous reviews in more than doubling the number of unbiased estimates of m analyzed [6,13]. In addition, our study helps to resolve the long-standing debate over whether prey or ratio dependence is the better simplification.…”
Section: Discussionsupporting
confidence: 91%
“…Introducing and applying an unbiased method to data from previous studies, they found that most data produced estimates of m that were statistically indistinguishable from ratio dependence ( m = -1) but significantly different from prey dependence ( m = 0). Through time, additional researchers have formulated other approaches to estimating m [13], and more studies have been conducted using a variety of methods. Since then, several studies have suggested that intermediate mutual interference (i.e., somewhere between 0 and -1) is likely to be more common than either pure prey dependence ( m = 0) or ratio dependence ( m = -1) [14-16]; however, no effort has been made yet to synthesize the new and expanding literature on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…The mass-specific consumption rate is described via a Beddington -deAngelis functional response [39]:…”
Section: (A) Population Dynamicsmentioning
confidence: 99%
“…The type III response is a sigmoid function. More functional responses have been described by various authors, all accommodating different mechanisms such as interference competition and different prey handling strategies, but type II is most commonly used (Skalski & Gilliam, 2001).…”
Section: Food Web In Mass Balancesmentioning
confidence: 99%